The Economic Effects of Judicial Accountability: Some Preliminary Insights - Stefan Voigt (Universität Kassel, Fachbereich Wirtschaftswissenschaften, 2005)
Judicial independence is not only a necessary condition for the impartiality of judges, it can also endanger it: judges that are independent could have incentives to remain uninformed, become lazy or even corrupt. It is therefore often argued that judicial independence and judicial accountability are competing ends. In this paper, it is, however, hypothesized that they are not necessarily competing ends but can be complementary means towards achieving impartiality and, in turn, the rule of law. It is further argued that judicial accountability can increase per capita income through various channels one of which is the reduction of corruption. First tests concerning the economic effects of JA are carried out drawing on the absence of corruption within the judiciary as well as data gathered by the U.S. State Department as proxies. On the basis of 75 countries, these proxies are highly significant for explaining differences in per capita income.
Keywords: K40; H11; P51; O40; 330; Judicial Independence; judicial accountability; rule of law; economic growth; corruption; constitutional political economy; Gerichtsbarkeit; Justiz; Verantwortung; Wirtschaftswachstum; Korruption; Schätzung; Welt